2006
DOI: 10.1074/jbc.m607524200
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane-proximal Region of the Thrombopoietin Receptor Confers Its High Surface Expression by JAK2-dependent and -independent Mechanisms

Abstract: Janus tyrosine kinase 2 (JAK2) is essential for signaling by the thrombopoietin (TpoR) and erythropoietin (EpoR) receptors. In the absence of JAK2 most EpoR molecules are retained in the endoplasmic reticulum in an Endo H-sensitive form. In contrast, we show that in the absence of JAK2 a large fraction of the TpoR is processed to the mature Endo H-resistant form and reaches the cell surface. By studying chimeras of the TpoR and EpoR we show that high surface expression of the TpoR is entirely conferred by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…We found that the N-terminal SH2-proximal region of this linker, residues P 501 KPKDKSNLLVF, was essential for interaction of JAK2 with the EpoR. These residues may be involved in direct binding to the membrane-proximal Box 1 region of cognate receptors or may hold the JAK N-terminal segment in the correct conformation to interact with cognate receptors (9,36,50). Four gain-of-function mutations in this linker transformed Ba/F3 cells, and three alanine-scanning mutants resulted in increased JAK2 activity.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We found that the N-terminal SH2-proximal region of this linker, residues P 501 KPKDKSNLLVF, was essential for interaction of JAK2 with the EpoR. These residues may be involved in direct binding to the membrane-proximal Box 1 region of cognate receptors or may hold the JAK N-terminal segment in the correct conformation to interact with cognate receptors (9,36,50). Four gain-of-function mutations in this linker transformed Ba/F3 cells, and three alanine-scanning mutants resulted in increased JAK2 activity.…”
Section: Discussionmentioning
confidence: 93%
“…EpoR surface expression was measured in the presence of wild-type or mutant full-length JAK2 or GST-JAK2(N) constructs in half a million ␄2A cells, as described previously (36).…”
Section: Jak2-dependent Epor Surface Expression-ha-taggedmentioning
confidence: 99%
See 1 more Smart Citation
“…12,28,29 To test whether JAK2 is required for TpoR activation by CALR mutants, we performed STAT5 transcriptional assays in the human JAK2-deficient g2A cells in the absence of JAK2 or using a TpoR receptor mutant that does not bind JAK2. CALR mutants could not induce TpoR activation in the absence of JAK2 (Figure 2A).…”
Section: Jak2 Is Required For Tpor Activation By Calr Mutantsmentioning
confidence: 99%
“…[8][9][10] Prior work has shown that the canonical ER-Golgi route for trafficking of Mpl to the cell surface is aberrant in myeloproliferative neoplasms, linked in part to requirements for WT Jak2 acting as a chaperone. 11,12 An alternative pathway to the surface for Mpl is provided by an unconventional autophagy-linked secretory pathway. 13 It is important to determine the functional impact of CAMT mutations on Mpl signaling and trafficking, because clinical presentation, disease progression, and treatment options reflect the underlying cellular mechanisms.…”
Section: Introductionmentioning
confidence: 99%